Nanocarrier-Based Transdermal Drug Delivery Systems for Dermatological Therapy - Yunxiang Kang; Sunxin Zhang; Guoqi Wang; Ziwei Yan; Guyuan Wu; Lu Tang; Wei Wang (MDPI AG, 2024)
Dermatoses are among the most prevalent non-fatal conditions worldwide. Given this context, it is imperative to introduce safe and effective dermatological treatments to address the diverse needs and concerns of individuals. Transdermal delivery technology offers a promising alternative compared to traditional administration methods such as oral or injection routes. Therefore, this review focuses on the recent achievements of nanocarrier-based transdermal delivery technology for dermatological therapy, which summarizes diverse delivery strategies to enhance skin penetration using various nanocarriers including vesicular nanocarriers, lipid-based nanocarriers, emulsion-based nanocarriers, and polymeric nanocarrier according to the pathogenesis of common dermatoses. The fundamentals of transdermal delivery including skin physiology structure and routes of penetration are introduced. Moreover, mechanisms to enhance skin penetration due to the utilization of nanocarriers such as skin hydration, system deformability, disruption of the stratum corneum, surface charge, and tunable particle size are outlined as well.